NORMA-NORMA DAN PERILAKU SEKS REMAJA - Masri Singarimbun (Populasi, 1991)
This article contains further analysis of a comparative study on adolecent reproductive health in four areas: urban and rural Yogyakarta, and urban (Denpasar) and rural Bali. Questions were asked on the attitudes and practice regarding premaritalintercourse, contraception and induced abortion. There were noticeable diffrentials by sex and area. Female respondents have much less sexual experince than male respondents, whereas rural respondents have less sexual experience than urban ones. With regard to attitudes on premarital intercource and induced abortion, Balinese respondents were more permissive than the Javanese. As a matter off act rural Balinese were more permissive than (urban) Yogyakarta respondents.